Performance Analysis of Surface Plasmon Resonance Waveguide for Sensing Applications - Teotia, Pradeep Kumar (My University, 2017)
Non-contact type of measurements with the help of optical technologies in the field of sensing and instrumentation has become a revolutionary idea in the present scenario. The advanced feature of optical fiber/waveguide such as exceptional senstivity and accuracy towards external environment has made research arena inevitable and forced us to develop a new thought. This property has given a way of a new variety of optical sensors which are free from electromagnetic interference. In parallel to these advantages, optical sensor technology has a perfect coordination between optoelectronic and fiber optic communication industry. Current scenario observes an improved quality of optical sensors which thereby increases the possibility to replace traditional sensors. Presently numerous research work are undergoing using fiber optic sensors with different interrogation techniques. Consequently, combination of optical fiber with material technology has also opened a new field to sensing platform. This thesis highlights the basic theory, fundamentals of SPR technology and the phenomena of SPR biosensor. This thesis also presents a new idea of performance analysis of Surface Plasmon Resonance waveguide for sensing applications. Multilayer grated structure is herby proposed as simple as versatile waveguide sensors. We further discuss the current developments and future applications of SPR based waveguide sensor. Different structures & geometry of grating and multilayer methods is investigated. The work gives an insight about the scope of metal slotted dielectric waveguide with a high refractive index material in which surface plasmon can propagate. Study of several symmetrical metal dielectric metal structures, it is analysed that slot waveguide geometry shows many intriguing properties with the use of high refractive index material that are not shown in the single interface metal dielectric. The surface plasmon resonance of slot MDM waveguide are studied and simulated using finite difference time domain method. High senstivity (≈ 200RIU−1) is exhibited by the proposed slot MDM waveguide geometry ≈ 200RIU−1) and higher transmission (≈ 10%) is also obtained. Geometry with different dielectric materials i.e. Air, Silicon-di-Oxide (SiO2) etc. has been investigated. The transmission has also been compared for slot MDM structures for different combinations Au−SiAirAu or vice versa. In multilayer grated structure, periodic gratings within the waveguide is inscribed in such a way that light prorogating inside the waveguide can interact with the surrounding environment, thus resulting in an output spectrum that includes changes due to the presence of all external parameters. Factors affecting the refractive index senstivity are explored through theory and simulation. Adding grating to the structure brings two advantages, firstly light can be coupled into surface plasmons by providing necessary phase matching and secondly they may further perturb the prorogation of the surface plasmons. One of the main aim of the present work is to study the different geometries to explore the senstivity and detection accuracy. We observed certain transmission characteristics for the respective designs. This thesis investigates the high performance of periodic grating coupled multi-layered SPR waveguide based on combination of aluminium and gold (Al+Au). High sensitivity is obtained by using grating filled with silver instead of air. Sensors performance is analysed by optimizing width and thickness of SPR active metal layer as well as the grating period. Using FDTD method, sensitivity and detection accuracy can be improved using appropriate multi-layered grating configuration in proportion. Grating based surface plasmon resonance waveguide biosensor for the detection of lung cancer biomarkers using Vroman effect is also reported. The proposed grating based multilayered biosensor is designed with high detection accuracy for Epidermal growth factor receptor and is also analysed to show high detection accuracy with acceptable sensitivity for lung cancer biomarkers i.e. CEA and EGFR. The introduction of periodic grating with metal multilayer generates a good resonance that helps in early detection of lung cancerous cells. Using finite difference time domain method, it is observed that wavelength of biosensor get red-shifted on variations of the refractive index due to the presence of both the lung cancerous bio-markers. The observed detection accuracy and sensitivity of proposed biosensor is quite acceptable for both lung cancer biomarkers i.e. Carcinoembryonic antigen and Epidermal growth factor receptor which further offer us label free early detection of lung cancer using these biomarkers. These sensors offer several advantages in bio-chemical sensing, chemical & food processing. The study suggests that SPR waveguide is useful for developing good sensitive systems. Most of the research findings of the thesis have been published in various SCI based international referred journals as per publication list.
Keywords: SPR; Waveguide Mode; TM Mode; Biosensor